2020
DOI: 10.1111/cyt.12824
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of an ulceroproliferative cervical mass

Abstract: A 75-year-old postmenopausal woman presented with the chief complaint of bleeding per vagina for the last 2 months. On examination, the patient had pallor. Per vaginal examination revealed an ulceroproliferative brownish-black growth at the posterior lip of the cervix measuring 3 × 3 cm. There was no inguinal lymphadenopathy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Studies in plant cell showed that, turgid cell containing cell sap with certain osmotic concentration when placed in solution of higher osmotic concentration (hypertonic solution) than the cell sap; exosmosis takes place and hypertonic solution try to become isotonic. The solution inside the cell sap is then replaced by the hypertonic solution as reported by Mitra et al, (1997).…”
Section: Over-all Acceptabilitymentioning
confidence: 99%
“…Studies in plant cell showed that, turgid cell containing cell sap with certain osmotic concentration when placed in solution of higher osmotic concentration (hypertonic solution) than the cell sap; exosmosis takes place and hypertonic solution try to become isotonic. The solution inside the cell sap is then replaced by the hypertonic solution as reported by Mitra et al, (1997).…”
Section: Over-all Acceptabilitymentioning
confidence: 99%